6z+9z=2z-3-5z

Simple and best practice solution for 6z+9z=2z-3-5z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6z+9z=2z-3-5z equation:


Simplifying
6z + 9z = 2z + -3 + -5z

Combine like terms: 6z + 9z = 15z
15z = 2z + -3 + -5z

Reorder the terms:
15z = -3 + 2z + -5z

Combine like terms: 2z + -5z = -3z
15z = -3 + -3z

Solving
15z = -3 + -3z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '3z' to each side of the equation.
15z + 3z = -3 + -3z + 3z

Combine like terms: 15z + 3z = 18z
18z = -3 + -3z + 3z

Combine like terms: -3z + 3z = 0
18z = -3 + 0
18z = -3

Divide each side by '18'.
z = -0.1666666667

Simplifying
z = -0.1666666667

See similar equations:

| 300*590= | | 3x-3y=4 | | 49-5x=4x+24 | | 4x+25=14x-95 | | 4x-4=36x+20 | | 1-3m= | | 19-4=72 | | 3(2x-4)=12 | | 11-10x=55-38x | | -24+6=3x+4-2x | | 7z-10-3z+2=0 | | -6-14= | | 15x+3=25+2x | | 35m^2-16m-3=0 | | 24(x+10)=-20(x-12) | | 8x+6=x+27 | | 11x-30=91 | | 4.5x-15=3x+4.5 | | 8x-7=9x | | -5+6= | | 12x-2(4x-5)=26 | | 13.56y-14.76=3 | | 27x-18y=32 | | 10x-96=6x+4 | | 7y+10-y=6+5y+6 | | 81-5x=40x+21 | | 3z+10-z=9+z-1 | | 10-10x=126-38x | | 2+2(x+3)= | | 108-5x=22x+21 | | 114-2x=25x+18 | | 2t^2-15t+22=0 |

Equations solver categories